2015
DOI: 10.1177/1071100715620423
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Osteochondral Transplantation for Osteochondral Lesions of the Talus

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…Current algorithms rely on the size and location of the defect to direct treatment recommendations [4][5][6][7][8] . Specifically, cartilage lesion size may be an important factor in determining clinical outcomes 9,10 . Preoperative magnetic resonance imaging (MRI) yields inaccurate estimates of lesion size and may overlook other defects in the knee [11][12][13][14] .…”
mentioning
confidence: 99%
“…Current algorithms rely on the size and location of the defect to direct treatment recommendations [4][5][6][7][8] . Specifically, cartilage lesion size may be an important factor in determining clinical outcomes 9,10 . Preoperative magnetic resonance imaging (MRI) yields inaccurate estimates of lesion size and may overlook other defects in the knee [11][12][13][14] .…”
mentioning
confidence: 99%
“…The resulting classifications were as follows: level 1, n = 2; level 2, n = 2; level 3, n = 3; and level 4, n = 2. All lesions were located in the centromedial zone . The autologous graft was taken from a knee that was asymptomatic preoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies showed that 63-85% of athletes who underwent AOT were able to return to preinjury levels of sports activity [59,61]. However, in a study by Paul et al [61], patients engaged in high-impact and contact sports required a partial modification of the sporting activities and a reduction of participation.…”
Section: Replacement Procedures Autologous Osteochondral Transplantationmentioning
confidence: 96%
“…A recent case series of 85 patients who underwent AOT found improved Foot and Ankle Outcome Score (FAOS) at mean 47.2 months of follow-up and MOCART scores postoperatively at mean 24.8 months of follow-up [59].…”
Section: Replacement Procedures Autologous Osteochondral Transplantationmentioning
confidence: 99%